2017
DOI: 10.1002/14651858.cd011686.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Triage tools for detecting cervical spine injury in pediatric trauma patients

Abstract: There are currently few studies assessing the diagnostic test accuracy of the NEXUS criteria and CCR in children. At the moment, there is not enough evidence to determine the accuracy of the Canadian C-spine Rule to detect CSI in pediatric trauma patients following blunt trauma. The confidence interval of the sensitivity of the NEXUS criteria between the individual studies showed a wide range, with a lower limit varying from 0.18 to 0.91 with a total of four false negative test results, meaning that if physici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 131 publications
(6 reference statements)
1
14
0
Order By: Relevance
“…In agreement with other authors and according to a Cochrane review, [ 13 ] we recommend obtaining cervical X-ray images in lateral projection, rather than open-mouth odontoid X-rays images, in children less than 8 to 10 years of age. [ 5 , 14 16 ] Frequently, the upper C-spine is not visualized clearly in the AP projection, and open-mouth X-ray images are difficult to obtain in young children.…”
Section: Discussionsupporting
confidence: 75%
“…In agreement with other authors and according to a Cochrane review, [ 13 ] we recommend obtaining cervical X-ray images in lateral projection, rather than open-mouth odontoid X-rays images, in children less than 8 to 10 years of age. [ 5 , 14 16 ] Frequently, the upper C-spine is not visualized clearly in the AP projection, and open-mouth X-ray images are difficult to obtain in young children.…”
Section: Discussionsupporting
confidence: 75%
“…3 Another retrospective case-control study 21 found that neither CCR nor NEXUS performed well enough to be used as designed in children younger than 10 years. A recent Cochrane review 16 identified similar concerns with both rules, finding insufficient evidence for use of CCR in paediatric cohorts, advising caution with NEXUS use in paediatric patients given sensitivity concerns and finding no evidence for use in children under 8 years. Future large multicentre studies are needed to assess individual CDR performance and projected effects on imaging rates across different paediatric age groups, with particular consideration given to younger cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…12 13 ED clinicians are thus faced with the decision of which children should receive imaging and for whom it can be safely avoided. [14][15][16] To address these concerns, attempts have been made to risk stratify patients with blunt trauma, identifying those at higher risk of CSI, and thus in need of imaging, through the use of clinical decision rules (CDRs). The most well known of these are the US derived National Emergency X-Radiography Utilization Study Low Risk Criteria (NEXUS) 17 18 and the Canadian C-Spine rule (CCR).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of these tools in children, however, is sparse. A 2017 meta-analysis concluded that the NEXUS criteria are at best a guide to clinical assessment, and not a strict protocol, while evidence for the accuracy of the CCR to detect CSI in the paediatric population is lacking [14]. Nevertheless, current international guidelines recommend combining both predicting rules [11,15,16].…”
Section: Introductionmentioning
confidence: 99%